P339 Factors of risky sexual behavior among long-haul truckers in a southern nigerian town. (14th July 2019) - Okojie, Paul; Okafor, Kingsley; Bello, Omoyemen; Ogboghodo, Esohe; Adesanya, Abimbola
Abstract : Background: Long-haul drivers play a role in the spread of sexually transmitted infections (STI) globally. Truck drivers engage in frequent travel away from home. They are exposed to risky sex with commercial sex workers who are a reservoir of HIV and other STIs. The study aimed to identify factors associated with commercial sexual exposure among long-haul truckers in a southern Nigerian town. Methods: A sample of 300 long-haul truckers from a highway park in Ahor, southern Nigeria was recruited in a cross-sectional study. An interviewer-administered questionnaire was used to collect socio-demographic and sexual risk behavior data. Data were analyzed with SPSS version 20 software. Chi-square test, Odds ratio, and confidence intervals were used to find the association between condom use, STI history, HIV status, duration of a trip, number of sexual partners, and truckers' exposure to commercial sex workers. Results: While 42.0% of the truckers used condoms, 58.0% were non-users. Reasons for non-condom use were commitment to partner (72.0%), lack of pleasure (21.0%), and beliefs (7.0%). Fifty percent of respondents reported two or less sexual contacts while a third of them reported 12 sexual contacts in 6 months. Overall, 59.0% of respondents had a history of multiple sexual partners. Factors associated with truckers' exposure to a commercial sex worker were use of psychoactive substance (OR 2.5 (1.5–4.4), p = 0.00; condom use (OR 16.3 (8.0–32.5), p = 0.00; previous sexually transmitted infection (OR 2.5 (1.2–5.1), p = 0.01. The odds of single-sex partner exposure to a commercial sex worker were 10% less than the odds in multiple sex partner truckers, p = 0.00. Conclusion: This study shows that psychoactive substances and condoms may be fueling exposure to commercial sex among truck drivers. Intervention programs should emphasize a single partner relationship, target substance users and highlight the potential impact of previous sexually transmitted infections on the risk of acquiring an HIV infection. Disclosure: No significant relationships.